The Role of Chaperones in Outer Membrane Biogenesis and Host Cell Interactions in Neisseria gonorrhoeae - Albalawi, Tawfiq (2025)
Neisseria gonorrhoeae, the gonococcus, is the aetiologic agent of the sexually transmitted disease gonorrhoea, which poses a global public health concern. Owing to the emergence of multidrug-resistant strains and the lack of an effective vaccine against this pathogen, novel interventions are required. The assembly of outer membrane proteins (OMPs) is essential for the survival and virulence of Gram-negative pathogens, such as N. gonorrhoeae. The periplasmic translocation and outer membrane (OM) assembly mechanism of OMPs is not completely understood, but it is dependent on the assistance of periplasmic chaperones. This study investigates the roles of three periplasmic chaperones -NGO1656, SurA and Skp - in the translocation and assembly of OMPs of N. gonorrhoeae, shedding light on their contributions to OM biogenesis and pathogenesis. To this end, the three chaperones were characterised by a bioinformatics approach to determine their degree of conservation across gonococcal strains. Subsequently, mutants of strain FA1090 with single or double knockouts of the periplasmic chaperones were generated using standard molecular biology techniques. Complemented derivatives of mutants were also constructed to validate the resulting phenotypes. The in vitro growth kinetics of the generated mutant and complemented strains were determined. The impact of individual or double deficiency of periplasmic chaperones on the overall OMP profiles was studied using SDS-PAGE. Moreover, the effect of the mutations on the assembly of individual OMPs, particularly those involved in iron acquisition, was tested using immunoblotting assays. The capacity of tested strains to colonise and invade host cells was examined by in vitro adhesion and invasion assays using human cervical carcinoma cells. Furthermore, biofilm formation was studied using a crystal violet assay. The results showed that NGO1656, SurA and Skp are highly conserved among gonococcal strains but are not essential for FA1090 viability under the conditions tested. The results of the 1D SDS-PAGE did not reveal any observable difference in OMP profiles between the mutant strains and the wild-type FA1090. However, immunoblotting analyses demonstrated that NGO1656 contributes to the translocation and assembly of transferrin-binding protein A (TbpA) and lactoferrin-binding protein A (LbpA), while Skp is the primary chaperone that contributes to the assembly and translocation of TbpB into the outer membrane. These results were confirmed by the reduced capacity of the mutant strains to use iron from human transferrin and lactoferrin in feeding assays. The three chaperones, especially NGO1656 were also shown to contribute to adhesion and possibly invasion. In addition, NGO1656 redundantly promotes the ability of gonococci to form biofilms together with SurA or Skp. Unlike E. coli SurA, N. gonorrhoeae FA1090 SurA does not appear to play a major role in translocation of OMPs to the outer membrane. These findings support the suggestion that the examined chaperones are viable options for therapeutic or preventive interventions against gonococcal infections, particularly when considered in the light of complementary data from other studies that demonstrated the chaperones are immunogenic and accessible to antibodies. This study reports for the first time on the contribution of NGO1656 in the acquisition of host-specific nutrients, adherence to host cells and biofilm formation in N. gonorrhoeae. Further investigations are needed to identify the exact role played by this periplasmic chaperone in these pathogenicity-related processes.